Neurological Mechanisms of Animal-Assisted Intervention in Alzheimer’s Disease: A Hypothetical Review - Kim, Sujin; Nam, Yunkwon; Ham, Min-Joo; Park, Chisoo; Moon, Minho; Yoo, Doo-Han (Frontiers in Aging Neuroscience, 2021)
Alzheimer's disease (AD) is an irreversible neurodegenerative brain disorder characterized by the aggregation of amyloid-beta (Aβ) and tau as the pathological hallmarks. AD accompanies cognitive decline as the major symptom and takes account of the majority of dementia. The failure of pharmacological approaches to treat AD has resulted in an increased focus on non-pharmacological interventions that can mitigate cognitive decline and delay disease progression in patients with AD. Animal-assisted intervention (AAI), a non-pharmacological intervention, improves emotional, social, and cognitive dysfunction in patients with neurodegenerative diseases. In particular, AAI has reported mitigating effects on cognitive impairment in patients with AD. Despite the positive effects of AAI on cognitive dysfunction in patients with AD, there is no study on how AAI affects AD-related pathologies. This review postulates neurological mechanisms of emotional or social interaction through AAI in countering AD-related pathology, such as Aβ deposition, tau hyperphosphorylation, neuroinflammation, and impaired adult hippocampal neurogenesis, and proposes insights for future research by organizing accumulated previous evidence.